Price Earning Ratio Fundamental Analysis of Food and Beverage Company Shares in Indonesia - Jariah, Ainun; Indrianasari, Neny Tri; Lukiana, Ninik (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2025)
The food and beverage (F&B) sector in Indonesia is a vital contributor to national economic growth due to the essential nature of its products, making it resilient even during crises such as the COVID-19 pandemic and global economic instability. However, stock price movements in this sector do not always reflect the companies’ fundamental performance. One key indicator used in fundamental analysis is the Price Earning Ratio (PER), which compares stock prices to earnings per share. PER is influenced by several factors including Return on Equity (ROE), Debt to Equity Ratio (DER), Current Ratio (CR), company size, profit growth, and macroeconomic indicators like inflation and exchange rates. This study aims to: (1) examine the effects of ROE, DER, CR, company size, and profit growth on PER, and (2) test whether profit growth mediates the relationship between ROE, DER, CR, company size, and PER. Using SEM AMOS for data analysis, the results indicate that CR and profit growth significantly affect PER. Furthermore, profit growth mediates the influence of DER and company size on PER. These findings suggest the importance of financial health and growth performance in determining stock valuation within the F&B sector.